KMDATA: a curated database of reconstructed individual patient-level data from 153 oncology clinical trials. (26th June 2021) - Fell, Geoffrey; Redd, Robert A; Vanderbeek, Alyssa M; Rahman, Rifaquat; Louv, Bill; McDunn, Jon; Arfè, Andrea; Alexander, Brian M; Ventz, Steffen; Trippa, Lorenzo
Abstract: We created a database of reconstructed patient-level data from published clinical trials that includes multiple time-to-event outcomes such as overall survival and progression-free survival. Outcomes were extracted from Kaplan–Meier (KM) curves reported in 153 oncology Phase III clinical trial publications identified through a PubMed search of clinical trials in breast, lung, prostate and colorectal cancer, published between 2014 and 2016. For each trial that met our search criteria, we curated study-level information and digitized all reported KM curves with the software Digitizelt . We then used the digitized KM survival curves to estimate (possibly censored) patient-level time-to-event outcomes. Collections of time-to-event datasets from completed trials can be used to support the choice of appropriate trial designs for future clinical studies. Patient-level data allow investigators to tailor clinical trial designs to diseases and classes of treatments. Patient-level data also allow investigators to estimate the operating characteristics (e.g. power and type I error rate) of candidate statistical designs and methods. Database URL : https://10.6084/m9.figshare.14642247.v1